Gadigaleyrodes froggatti, a new genus and species of whitefly - Dooley, John W. Iii; Gillespie, Peter (Zootaxa, 2013)
A new monotypic genus of whiteflies (Aleyrodidae), Gadigaleyrodes gen.n., is described and illustrated for G. froggatti sp.n. from New South Wales, Australia. Specimens were collected by W. W. Froggatt in 1899 on Syncarpia glomulifera, and subsequently by P. S. Gillespie on an unknown climbing plant. The genus has unusual morphological features with traits common to both Aleurodicinae and Aleyrodinae. The subfamily placement is discussed, and a key provided to discriminate this taxon from similar whitefly genera in Australia.